Community Education on the Effects of Cigarette Smoke on Lung Tissue and the Preventive Role of Green Apple (Malus domestica) Juice - Pranata, Chandra; Darmirani, Yosi; Pratiwi, Asti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2025)
Cigarette smoke contains a large number of oxidants or free radicals, along with approximately 4,700 harmful chemical substances. An increase in free radical levels in the body can trigger the formation of Reactive Oxygen Species (ROS), which contributes to oxidative stress, especially when there is an imbalance between oxidants and antioxidants. During this process, oxygen (O?) may leak and convert into superoxide radicals (O??), which can stimulate The synthesis of pro-inflammatory mediators like interleukin-6 (IL-6). In this research aims To assess the impact of cigarette smoke exposure on the histological structure of lung tissue in laboratory rats. A Community Service Activity (PkM) involving 70 residents of Pantai Labu Subdistrict Aimed at promoting public awareness regarding the importance of adopting a safe and healthy lifestyle. During the activity, participants received education regarding The damaging influence of cigarette smoke on the body, particularly on, as well as potential of green apple juice as a natural alternative to support lung health. The educational materials included information on the safety and stability of green apple juice consumption, and the importance of maintaining an appropriate acidity level (pH) that aligns with lung health. Through pre-test and post-test assessments, there was a 50% and 30% increase in participants' knowledge, respectively, indicating that the program was effective in improving public understanding of the dangers of cigarette smoke on lung health. In addition, green apple juice was introduced as a promising natural alternative to support the histopathological repair of organs. The PkM team also encouraged the community to adopt a healthier lifestyle, be more selective, and remain cautious about exposure to cigarette smoke in their environment.